Effect of Protic Ionic Liquids in Sugar Cane Bagasse Pretreatment for Lignin Valorization and Ethanol Production - Pin, Thaynara C.; Rabelo, Sarita C. [UNESP]; Pu, Yunqiao; Ragauskas, Arthur J.; Costa, Aline C. (American Chemical Society (ACS), 2021)
Ionic liquids have been called designer solvents because it is possible to fine-tune their properties from a huge range of possible combinations of cations and anions. In this work, we evaluate the potential of protic ionic liquids (PILs) in the fractionation of sugar cane bagasse in a biorefinery context. The PILs were designed to selectively solubilize lignin and leave a polysaccharides solid fraction. The carbohydrate fraction was further hydrolyzed to obtain pentose and hexose sugars, which were fermented using a pentose-consuming yeast. The results have shown that, differently from pretreatments that solubilize hemicelluloses, pentoses could be fermented together with hexoses without a prior detoxification step with high yield and productivity. The lignin recovered was characterized by 2D HSQC NMR, 31P NMR, and GPC, showing that the design of the PIL influences lignin characteristics, but pretreatment temperature and time do not. The lignins obtained are sulfur-free, and the richness of their functional groups makes them attractive for conversion into a diversity of value-added products, which can make a biorefinery based on the proposed process viable.
Keywords: biomass; enzymatic hydrolysis; ethanol production; lignin; protic ionic liquid